UTILIZATION OF WATER ON MINE TIN AS A SUPPLEMENT OF SOIL WATER SOURCES USING COMPOST HOLE IN BANGKA BELITUNG - Meyzilia, Arvina (JURNAL PENDIDIKAN ILMU SOSIAL, 2018)
The aim of this research is to analyze the utilization of compost pits as a neutralization of tin metal content in ex-tin mining water. This research method is survey and literature study. The results showed that the lead content in water under tin mining can be neutralized by using compost. Tin mining extracts that have been handled with compost pits can be used as additional reserves of ground water sources in Bangka Belitung. However, the use of compost pits still has some constraints that require further research.